Implementasi Prinsip Nilai dan Etika Pekerja Sosial dalam Penanganan Pengemis di IPSM Yogyakarta - Novie Purnia Putri (Islamic Management and Empowerment Journal, 2019)
Social work is as a help profession. It has a basic task in overcoming social problems, one of them is handling the beggars. The method used in this study was a qualitative method by describing the implementation of the value principles and ethics of social workers in handling the beggars through the Yogyakarta Society of Social Workers Association and the ethical dilemmas inside. The purpose of this study was expected to provide an overview of practices in the field as an effort to improve the quality of social work, increasingly to have adequate competence, both in terms of values and ethics in carrying out their profession. The results of this study indicated that in the implementation of the value principles and ethics of social workers with reviews of acceptance, individualization,  disclosure of feelings, non-judgmental attitudes, objectivity, self determination, confidentiality and accountability. The whole principles had been practiced. However, during practicing in the field, there were ethic dilemmas in the application of the principles. They were dilemmas in client confidentiality, policy laws, management care and scarce and limited resources.